STUDY OF OCEAN CIRCULATION IN INDONESIAN ARCHIPELAGO SEA USING THREE DIMENSIONAL OCEAN MODEL - Nurweda P.,, I Dewa Nym.; Osawa, Takahiro; Arthana, I Wayan (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 4 No 2, 2012)
The Regional Ocean Modeling System (ROMS) was used to simulate the Indonesian Archipelago Sea current and temperature with two different vertical mixing schemes. One corresponds to the newly developed K-Profile Parameterization (KPP) scheme and the other is adapted from the stability frequency of Brunt-Vaisala Frequency mixing (BVF). It is found that, both of schemes produce reasonably realistic sea surface temperature (SST); however, the root mean square error (RMSE) values from the BVF vertical mixing were less than the KPP vertical mixing. The RMSE values from the BVF vertical mixing at northwest and southeast monsoons can be reduced down to 5.1607E-01 0C and 5.7639E-01 0C respectively. These validation results reveal that accuracy of the BVF vertical mixing is better than the KPP vertical mixing.The model results based on the BVF vertical mixing scheme show that the direction of Java Sea, Karimata and Sunda Straits surface current are strongly affected by the zonal wind system. The direction of surface current was change following the monsoonal wind system. On the other hand, the Makasar Strait surface current tend to flow southward throughout the year with annual variations in transport are related dynamically to the monsoon winds. These southward surface currents are known as Indonesian Through Flow (ITF) and it is governed by strong pressure gradient from the Pacific to the Indian Oceans. The signals of El Nino 2002 event also can be detected by the model results. It recognized that the strong Equatorial Counter Current flows to eastward to the central part of the Pacific Ocean. The Makasar Strait surface current was stronger than usual but the Karimata Strait surface current was weaker during this period.
Keywords: Regional Ocean Modeling System, vertical mixing, sea surface temperature, sea surface current.